The effect of milling time on formation of magnesium-activated carbon composites as hydrogen absorbing materials. Issue 1 (February 2021) - Mulana, F; Sofyana,; Mariana,; Azwar,; Mustanir,; Jalil, Z
Abstract: Hydrogen is a potential environmentally friendly fuel, but it has problems in terms of storage. Hydrogen storage using magnesium (Mg) and activated carbon (AC) is an effective and safe alternative because it can store hydrogen in a large enough capacity. This research was conducted to study the potential of Mg-AC material with addition of cobalt as catalyst in storing hydrogen by studying the effect of milling time and weight ratio of Mg-AC on the characteristics of the composites and the amount of hydrogen gas that can be adsorbed. Composites were formed using mechanical milling method using Fritsch 6 Planetary Ball Mill. The prepared composites were characterized using the X-ray diffraction (XRD), Fourier Transform Infra-Red (FTIR), Scanning Electron Microscopy (SEM) and Thermal Gravimetric Analysis (TGA). XRD analysis showed that MgH2 compound was formed starting from 3 hr of milling time. The results of FTIR characterization showed that more C-H groups were formed with increasing milling time. The SEM graphs show that the longer milling time, the more evenly the distribution of particles in the Mg-AC composite and forming more nano particles. Meanwhile, the TGA analysis showed that with the addition of 5% AC, 10% and 15% then a weight reduction reached 9.6%, 10.6% and 14.2%, respectively.